Beyond Cost Savings: The Impact of Open Textbooks on Writing Studies Course Grades - LeMire, Sarah (Evidence Based Library and Information Practice, 2024)
Objective – This study was designed to explore the potential academic impact of open textbooks in writing courses. Methods – The researcher used statistical analyses of course outcomes for over 1,000 sections to examine the impact of OER usage on course GPA in three writing courses at an R1 university. Results – Study results reveal that using an OER textbook is associated with an overall increase in class GPA. Conclusion – When advocating for the use of OER in campus writing courses, librarians can point to findings that suggest improved student outcomes after a switch to OER in those courses.